Zur Krisensituation der arabischen Gesellschaften - Alnasseri, Sabah (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
If anything brings the construction Bin-Laden discoursivly to the fore it is a specific conflict situation with the participation of the USA in the arabic space: a conflict situation between the dominant political regimes, the opposing conservativ-liberal blocks, and an extremist wing. The conflict could be characterized as between two political strategies about the restructuring of this economic as well as geostrategic important space. The construction Bin-Laden is the name of this violence game.